Design and Implementation of a Web-Based Waste Management Information System to Improve Operational Efficiency at the Environmental Agency of Minahasa Utara Regency - Rolando Ariesky Gans; Juan Mark Jevlands Carlos; Zefanya Mandagi; Ottopianus Mellolo; Sintya Paula Junaedy (Journal of Social Research, 2026)
Waste management in Minahasa Utara Regency faces operational challenges including the lack of an integrated digital information system, manual record-keeping processes, and limited real-time monitoring capabilities for waste collection activities. This study presents the design and implementation of a web-based waste management information system for the Environmental Agency (Dinas Lingkungan Hidup) of Minahasa Utara Regency. The system was developed using the PHP Laravel framework with a MySQL relational database and deployed on a local server within the agency's network infrastructure. Key modules implemented include waste collection scheduling, route management, vehicle and personnel tracking, report generation, and a public-facing waste complaint submission portal. The system was evaluated through functional testing using the black-box method and usability testing using the System Usability Scale (SUS) questionnaire administered to 15 agency staff members. Functional testing results show a 100% pass rate across all 42 test cases. The SUS score of 81.3 out of 100 places the system in the "Excellent" usability category. The implementation demonstrates significant improvements in operational documentation efficiency, reducing daily report preparation time by an estimated 65% compared to the previous manual process. The system provides a scalable and maintainable digital platform for modernizing waste management operations in the regency.